Life-Threatening Complications of Hormonal Contraceptives: A Case History - Saheed Khan; Yvo M. Smulders; Johanna I. P. de Vries; Angélique M. E. Spoelstra-de Man (Hindawi Limited, 2013)
We present a case with the rare combination of thrombotic and hemorrhagic complications of oral contraceptives. A healthy 40-year-old woman suffered from cardiac arrest due to massive pulmonary embolism, caused by oral contraceptives and immobilization during a flight. After successful resuscitation, obstructive shock necessitated thrombolysis and thereafter heparin. Anticoagulation was complicated by internal bleeding from contraceptive related hepatic adenoma. She underwent arterial embolisation, and anticoagulation was continued. On day 18, she was discharged in a good condition. Hepatic adenomas are a potential source of internal bleeding in women using oral contraceptives requiring anticoagulation. Signs of internal bleeding in such patients should prompt immediate abdominal ultrasound examination.